Application of the Rational Unified Process Method in Web Service Development Payment System Integration with Multibank Virtual Accounts - Sopingi; Ety Meikhati; Wijiyanto (Politeknik Piksi Ganesha Indonesia, 2021)
The Payment System is a series of interconnected components consisting of rules, institutions, and procedures used for money transactions in fulfilling the obligations of economic activities. The Duta Bangsa University of Surakarta is a case study in this research where the student payment system is still a billing system. The faculty finance department gives bills tuition fees to students one by one. Moreover, it determines the bank used for payments. It resulted in quite many queues when filling out the study plan card (KRS) and exams. This research aims to produce a web service application and standardization with good performance in the payment process at Duta Bangsa University through virtual accounts from various banks and payment channels. The method used to achieve the authors' goals in this study is the Rational Unified Process (RUP) method. The research result is a web service application that can make invoices, inquiries, payments, and reversals of various bank payment channels. The User Acceptance Test results show a very agreeable value of 94.17%, so that the web service is feasible for the production version application. While testing the response time to measure performance for 7 (seven) days, the average response time was 0.49809 seconds.